The murder of Mr. Ma - Nee, John Shen Yen; Rozan, S. J. (Soho Crime, 2024)
In 1924 London, when shy academic Lao She meets larger-than-life Judge Dee Ren Jie, these unlikely allies investigate the murders of Chinese immigrants, all stabbed to death with a butterfly sword and must connect the dots to catch a killer before they become victims themselves.